Animação Audiovisual Paraense: formação do campo e narrativas quadro a quadro - DUARTE, Andrei Miralha Padilha (Universidade Federal do Pará, 2019)
The word animation comes from the latin term "anima," which means "soul" in the sense of "breath of life." According to Perisic (1979), animation is a way of creating an illusion, giving "life" to inanimate objects – real / virtual objects or simply freehand or computer drawings. Born of the mix between art and technology, the animation films come in the late nineteenth century, and developed throughout the twentieth century in numerous productions around the world. However, it is only at the beginning of the 21st century that the first animated short films were produced in brazilian State of Pará. This research includes the formation of the State of Pará's field of animation, according to Pierre Bourdieu. It gathers narratives about the production of animations carried out until 2018, considering the networks of personal relationships, the formation of groups, as well as the techniques and methodologies used to carry out each work. I carry out this study through participatory field research, interviews, bibliographical and film research, observing sociocultural events, characters, productions, policies and institutions that contributed to the development of the animation in the State of Pará.